Solvent Extraction of W(VI) with Malachite Green into Nitrobenzene - Patil, V.B.; Turel, Z.R. (Asian Journal of Chemistry, 2010)
A rapid and selective method has been developed for the extraction of W(VI) with malachite green into nitrobenzene. The effect of various parameters on the extraction coefficient value such as effect of pH, time of equilibration, effect of various cations and anions have been evaluated. The stoichiometry of metal to reagent determined by the method of substoichiometric extraction was found to be 1 : 1. It was further supported by the slope ratio method.